Upaya Pencegahan Perdarahan Ibu Post Sectio Caesarea Dengan Anemia Di Rsu Assalam Gemolong - Arlinda, Anisa Nila; Sulastri, Sulastri, S.Kp., M.Kes (2016)
Bleeding after childbirth is the highest cause of maternal death composed to other causes. Anemia is one of the causes of the occourence of bleeding. If the levels of Hb less than 7 g/dl or hematokrit less than 20 % then it says severe anemia and handling should be done soon as possible. The addition of food that is nutritions and protein is one way to prevent the occurance of unbleeding. Consume foods containing vitamin C was instrumental in the formation of hemoglobin and vitamin K can help in blood clotting. Purpose: The goal of nursing care in patient post sectio caesarea with anemia is to prevent the occurence of bleeding. Method: The method used is descriptive by means of collecting data, analyzing the data, and the conclusion. Result: After nursing care for 3x24 hours obtained result patially resolved the nursing problem, requiring further thretment and cooperation of patient and families who are indispensable to the success of nursing care. The existence of non pharmacological theory against the influence of the risk of bleeding. Patients are encouraged to perform independently.